1981
DOI: 10.1093/oxfordjournals.aob.a086004
|View full text |Cite
|
Sign up to set email alerts
|

Growth Rate and Water Relations of Citrus Leaf Flushes*

Abstract: Growth rates of seasonal leaf flushes of 'Valencia' orange [Citrus sinensis (L.) Osbeck] were measured and water relations characteristics of young (new) and over-wintered (old) citrus leaves were compared. New flush leaves had lower specific leaf weights and lower midday leaf water potentials than comparably exposed old leaves. Spring and summer flush new leaves had higher osmotic potentials than old leaves. These differences became non-significant as the new leaves matured. During summer conditions, water. s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
19
1
2

Year Published

1982
1982
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 13 publications
4
19
1
2
Order By: Relevance
“…The typical response is wilting in the older leaves before the younger leaves. This study and others (13,15) suggest that there may be two different responses to water stress, depending on the reproduction strategy of the species. Under water stress, plants reproducing by seed only, which include many agricultural plants, will maintain flow to the apical meristem to sustain leaf, flower, and soed production.…”
Section: Resultssupporting
confidence: 54%
See 2 more Smart Citations
“…The typical response is wilting in the older leaves before the younger leaves. This study and others (13,15) suggest that there may be two different responses to water stress, depending on the reproduction strategy of the species. Under water stress, plants reproducing by seed only, which include many agricultural plants, will maintain flow to the apical meristem to sustain leaf, flower, and soed production.…”
Section: Resultssupporting
confidence: 54%
“…Catsky (5) noted that young leaves received a preferential portion of the water supply and that, under large water deficits, water was translocated from older leaves to younger leaves. Lockhart (11) suggested that this phenomenon would occur if the cells in both young and mature tissue had the same g. More recently, the reverse response, initial wilting in young leaves, has been observed in several perennial plants, tea (13), and orange and grapefruit (15 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research for citrus trees suggested that the minimum water potential value at wilting point can be down to −1.7 MPa for young leaves, and −1.9 MPa to −2.6 MPa for mature leaves (Syvertsen et al, 1981;Syvertsen, 1982). It is also reported that citrus trees under regulated deficit irrigation can have a threshold stem water potential of −1.84 MPa (Ballester et al, 2014).…”
Section: Stem Water Potential and Deep Layer Soil Water Centent Data mentioning
confidence: 99%
“…O estudo das relações hídricas é realizado a partir do monitoramento de variações na transpiração, potencial de água na folha ou ramo, condutância estomática e umidade do solo e ar (COHEN et al, 1997;KAUFMANN;HALL, 1972;KAUFMANN, 1975;LEVY, 1980;MACHADO et al, 2002MACHADO et al, , 2006SYVERTSEN, 1982;ALBRIGO, 1980a;ALLEN, 1981). Considerando um continuum de água no sistema solo-planta-atmosfera (ANGELOCCI, 2002;NOBEL, 1999), as inter-relações entre as variáveis fisiológicas e ambientais podem ser sumarizadas da seguinte forma: (a) a baixa disponibilidade de água no solo reduz a absorção de água pelas raízes, ocasionando menor hidratação da parte aérea (verificado pelos baixos valores de potencial de água na folha ou ramo).…”
Section: Introductionunclassified